Determining minimal inhibitory concentrations and antibiotic susceptibility for Enterobacterales by flow cytometry using reactive oxygen species as a marker - Jia Hao Yeo; Nasren Begam; Wan Ting Leow; Andrea Lay-Hoon Kwa (PLoS ONE, 2025)
Early appropriate antibiotic treatment is vital in reducing patient mortality. However, current antimicrobial susceptibility testing (AST) requires 16–24 hours of incubation, delaying appropriate antibiotic treatment. Flow cytometry (FCM) is a rapid method in assessing fluorescence (such as fluorophores for ROS) at single-cell resolution. Reactive oxygen species (ROS) are oxygen-containing molecules, which are inducible by antibiotics and potentially bactericidal. We asked if FCM measurements of ROS in antibiotic-treated bacteria could be used in determining antibiotic MIC as an alternative to conventional AST. This study aims to develop and evaluate the feasibility of a FCM assay to determine antibiotic susceptibility accurately with a short turn-around time. MICs of amikacins, aztreonams, cephalosporins (with or without a lactamase inhibitor), carbapenems, levofloxacin, polymyxin B, trimethoprim/sulfamethoxazole, and tigecycline were determined for six clinical carbapenem-resistant Enterobacterales isolates using conventional microbroth dilution assays and using FCM assessments in parallel. Accurate MICs determined using FCM is defined as MICs falling within 2-fold dilutions of the conventional microbroth dilution AST assay. MIC determination via ROS measurements were mostly accurate for carbapenems (22/24; 91.7% accuracy) and trimethoprim/sulfamethoxazole (5/6; 83.3% accuracy). In contrary, ROS levels were less accurate in determining MICs for amikacin (4/6; 66.7% accuracy), aztreonam (4/6; 66.7% accuracy), cephalosporins only (5/12; 41.6% accuracy), cephalosporin with lactamase inhibitor (11/18; 61.1% accuracy), polymyxin-B (2/6; 33.3% accuracy), levofloxacin (1/6; 16.7% accuracy), and tigecycline (2/6; 33.3% accuracy). These data support that ROS assessments using FCM is suitable for accurately determining MICs for carbapenems in Enterobacterales. Further optimisation and validation of this FCM assay with additional bacteria strains with varying antibiotic susceptibilities are warranted. Future studies include assessing other organisms and antibiotic pairs.